IGF-1, Inflammation and Retinal Degeneration: A Close Network - Arroba, Ana I.; Campos-Caro, Antonio; Aguilar-Diosdado, Manuel; Valverde, Ángela M. (Frontiers in Aging Neuroscience, 2018)
Retinal degenerative diseases are a group of heterogeneous diseases that include age-related macular degeneration (AMD), retinitis pigmentosa (RP), and diabetic retinopathy (DR). The progressive degeneration of the retinal neurons results in a severe deterioration of the visual function. Neuroinflammation is an early hallmark of many neurodegenerative disorders of the retina including AMD, RP and DR. Microglial cells, key components of the retinal immune defence system, are activated in retinal degenerative diseases. In the microglia the interplay between the proinflammatory/classically activated or antiinflammatory/alternatively activated phenotypes is a complex dynamic process that occurs during the course of disease due to the different environmental signals related to pathophysiological conditions. In this regard, an adequate transition from the proinflammatory to the anti-inflammatory response is necessary to counteract retinal neurodegeneration and its subsequent damage that leads to the loss of visual function. Insulin like-growth factor-1 (IGF-1) has been considered as a pleiotropic factor in the retina under health or disease conditions and several effects of IGF-1 in retinal immune modulation have been described. In this review, we provide recent insights of inflammation as a common feature of retinal diseases (AMD, RP and RD) highlighting the role of microglia, exosomes and IGF-1 in this process.